Operation pangolin : saving the world's only scaled mammal - Eszterhas, Suzi (Millbrook Press, 2023)
"Pangolins are one of the most poached animals in the world. Yet scientists know very little about them. Discover how pangolin rescuers and researchers such as Thai Nguyen are working to protect these mysterious creatures"--